2017
DOI: 10.1002/hep.29302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laboratory tests, ultrasound, or magnetic resonance elastography to detect fibrosis in patients with nonalcoholic fatty liver disease: A meta‐analysis

Abstract: MRE and SWE may have the highest diagnostic accuracy for staging fibrosis in NAFLD patients. Among the four noninvasive simple indexes, NFS and FIB-4 probably offer the best diagnostic performance for detecting AF. (Hepatology 2017;66:1486-1501).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
656
5
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 721 publications
(693 citation statements)
references
References 35 publications
11
656
5
21
Order By: Relevance
“…However, VCTE requires a specialized device, and cannot properly assess hepatic fibrosis in patients with ascites and obesity . Whereas two‐dimensional shear wave elastography (2D‐SWE) is a form of elastography, and is a useful non‐invasive method for the diagnosis of hepatic fibrosis . SWE can be performed with a regular ultrasound examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, VCTE requires a specialized device, and cannot properly assess hepatic fibrosis in patients with ascites and obesity . Whereas two‐dimensional shear wave elastography (2D‐SWE) is a form of elastography, and is a useful non‐invasive method for the diagnosis of hepatic fibrosis . SWE can be performed with a regular ultrasound examination.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, liver stiffness, as measured by SWE, is less affected by ascites and subcutaneous fat than VCTE . Recently, a meta‐analysis showed that SWE has higher diagnostic accuracy for staging fibrosis compared with VCTE …”
Section: Introductionmentioning
confidence: 99%
“…9,10 TE is widely used because of its reproducibility and excellent interand intraobserver agreement, and it has been validated in enormous numbers of studies, which showed a very good correlation to histological assessment by liver biopsy. [15][16][17][18][19] However, the data regarding diagnostic performances of FIB-4 and APRI score compared with TE are limited. 8 Another currently available noninvasive method is the serum biomarkers of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that the sensitivity of serum ATX was high at all stages of fibrosis and was highest for the diagnosis of ≥stage 2 and ≥stage 3 in both men and women (Table ). There have been many reports regarding methods for the diagnosis of advanced fibrosis (≥stage 3) . However, Hagström et al .…”
Section: Discussionmentioning
confidence: 99%